HAK ASUH ANAK PASCA PERCERAIAN MENURUT KOMPILASI HUKUM ISLAM: ANALISIS YURIDIS DAN KONSEPTUAL - Suryantoro, Dwi Dasa (Universitas Nurul Jadid, 2024)
Children are the crown of a family. However, the journey of a household sometimes has to end with the divorce of both parents, so that the child's right to get parental affection is neglected. The purpose of this study is to determine the custody rights of children after the divorce of their parents. The method used is normative juridical research method with legislative approach and conceptual approach. The results showed that Article 105 of the Compilation of Islamic Law (KHI) states that the mother has the full right to obtain custody of children after divorce. important conditions must be met to achieve the objectives of Article 105 KHI. Therefore, the mother as the bearer of the mandate must be able to legally prove all her actions, especially those that ensure the survival of the child. In this case, the mother has the legal authority to take care of him. The mother may exercise her rights as a child custodian unless the mother does not have good faith towards her child.